MANAGEMENT OF 3D CONFORMAL RADIOTHERAPY IN PATIENT WITH NASOPHARYNGEAL CARCINOMA IN SUB DEPARTMENT OF RADIOTHERAPY RUMKITAL DR. RAMELAN - Anis Istiawan; Jeffri Ardiyanto; Ardi Soesilo Wibowo (Poltekkes Kemenkes Semarang, 2018)
Background: Nasopharyngeal carcinoma is the most common malignant tumor among malignant ENT tumors in Indonesia, where nasopharyngeal carcinoma is included in the top five largest malignant tumors with the highest frequency, whereas in the head and neck areas occupy the first place. The purpose of this study is to know the 3D-CRT management in patients with nasopharynx carcinoma and to know the result of manual radiotherapy verification process using Image Computed Radiography Portal at Sub Department Radiotherapy Rumkital Dr. Ramelan.Methods: This research type is qualitative with case study approach. The study subjects were 1 person nasopharyngeal carcinoma patients. The subjects of the study were 2 person oncologist, 1 medical physicist, 3 radiotherapy radiograph (RTT). Data were collected by observation, interview and documentation. Data analysis is done descriptivelyResult: The results showed management of 3D conformal nasopharyngeal carcinoma in Rumkital Radiotherapy Sub Department was in accordance with the literature and manual radiotherapy verification with Image Computed Radiography (PICR) Portal in Sub Department of Radiotherapy. Ramelan result can be accepted as replacement of Electronic Image Image Device (EPID).Conclution: result of management 3D conformal nasopharyngeal carcinomal can be accepted as replacement of Electronic Image Image Device (EPID)